POTENSI DAN ETNOBOTANI AGATHIS DI HUTAN PENDIDIKAN FAKULTAS PERTANIAN UNPATTI DI NEGERI HONITETU - Ludia Siahaya; Febian F. Tetalay; Vantri Eluwar; Patriarex Polhaupessy; Chrisalfa L. Louhenapessy (Lambung Mangkurat University-Indonesia, 2021)
The research about Agathis potential and Etnobotany at Education Forest aimed to get data of Agathis sp potential and etnobotany in the Education Forest, Agriculture Faculty, Pattimura University at Honitetu Village. The method used was quantitative descriptive method and qualitative description. To obtain Agathis potential data, a survey technique was carried out and continued by analyzing the data using the Important Value Index to determine its ecological potential. To determine the economic potential of timber forest products by calculating the volume of wood per hectare and non-timber forest products by calculating the dammar yield obtained. Etnobotany data were collected through interview techniques which were then analyzed and described. Based on the Importand Value Index (IVI), the ecological potential of Agathis increases its dominance value at a higher growth rate. At the seedling level, Agathis occupies the 9th position, at the stake level occupies the 8th position, at the pole level occupies the 5th position, and at the tree level occupies the 2nd position. The economic potential of Agathis timber forest products based on of the volume of wood is 1.000359 m3 / ha. The economic potential of Agathis non-timber forest products for 40 trees can be obtained 120 - 240 kg per 3 months or Rp 4,800,000 to Rp 9,600,000 per year. Gum resin in daily life is used as a fire starter (“tompong api”), torch (lighting) at nihgt, glue (adhesive) and sold as a source of community income. Effort to maintain its sustainability through “Sasi Gereja” and conducting cultivation using natural extraction by individual communities.